Fake news against the Republic: The ABC as a collaborator and agitator of the coup of 1936 - Noguerales García, Lucía (Hispania Nova, 2021)
This research project proposes to analyze the role of the ABC as a collaborator and agitator of the coup of 1936 by publishing false, exaggerated or unverified information in order to create a climate of opinion favourable to the uprising against the republican regime. The chosen methodology is the case study and the content analysis of 177 news, editorials, opinion articles, electoral propaganda and political speeches published in this newspaper from the 6th of February to the 19th of July 1936.
Keywords: ABA; coup; propaganda; Second Republic; violence; fake news